THE INFLUENCE OF COMPENSATION ON EMPLOYEE PRODUCTIVITY IN PANDEMIC ERA AT PT TERANG MULIA GAS MANADO - Marchellino Xaverius Yonathan Lala (Universitas Sam Ratulangi, 2022)
This study aims to analyze the influence of compensation on PT Terang Mulia Gas Manado productivity in pandemic era. This research is a qualitative research methodology which is descriptive research and takes about 6 informants as permanent employees who actively work in PT Terang Mulia Gas Manado. In this research, the data used in this research consist of two types of data, which is primary and secondary data. Primary data are gained from in-depth interviews and secondary data are taken from several books, journals, and previous research. Based on the results of data analysis and discussion, it can be withdrawn the conclusion that. Compensation is capable of exerting considerable influence to increase employee work productivity, at PT Terang Mulia Gas Manado. The existence of compensation will provide good benefits to the performance of employees, the Company will get and maintain the existence of employees with good quality. The company can spur employee performance by direct compensation also indirect compensation based on the company’s policies and company’s work motivations.